Characterising immersive argument-based inquiry learning environments in school-based education: a systematic literature review. Issue 1 (2nd January 2022) - Weiss, Kathleen A.; McDermott, Mark A.; Hand, Brian
ABSTRACT: Educational initiatives in multiple disciplinary areas call for student engagement in the practice of argumentation (CCSSI, 2010a, 2010b ; Mullis & Martin, 2017 ; NGSS Lead States, 2013 ; OECD, 2018 ). In science education, immersive argument-based inquiry (ABI) is one category of approaches which integrates argumentation in all classroom activity in order to support conceptual understanding in science. Previous research has reported details of specific immersive ABI approaches but has failed to summarise the characteristics common to all approaches categorised this way and the critical components underlying the learning environments supporting these approaches. This study identified common elements of immersive ABI learning environments through a systematic literature review of 16 existing approaches. Open and axial coding led to the identification of three categories of common elements, including student actions, teacher actions, and generative opportunities. Implications and potential steps to build further understanding of the common elements are discussed.